Influence of crystallinity on the dielectric relaxations of poly(butylene succinate) and poly[(butylene succinate)-co-(butylene adipate)]. (November 2016) - Charlon, Sébastien; Delbreilh, Laurent; Dargent, Eric; Follain, Nadège; Soulestin, Jérémie; Marais, Stéphane
Graphical abstract: Highlights: Amorphous and semi-crystalline PBS and PBSA are studied with DSC and BDS. The three-phases model is applied to quantified the different phases. 21 mol% of butylene adipate decreases the crystallinity degree and the crystal sizes. Segmental dynamics of amorphous phase are identical whatever crystallinity degree. New local motions in amorphous phase due to presence of crystals is detected. Abstract: Amorphous and semi-crystalline poly(butylene succinate) (PBS) and poly[(butylene succinate)- co -(butylene adipate)] (PBSA) are studied with Differential Scanning Calorimetry and Broadband Dielectric Spectroscopy (BDS). It was shown that 21 mol% of butylene adipate group decreases drastically the degree of crystallinity and the size of the crystal lamellae of the PBSA. For the two semi-crystalline polymers, the microstructure is well described by a three-phase model including a small degree of rigid amorphous fraction. Fragility indexes of the main dielectric relaxation are identical for each sample which shows similar segmental dynamics of their amorphous phase. BDS allows detecting complex secondary relaxations in semi-crystalline PBS and PBSA. Local motions are impacted by the microstructure and a new relaxation occurs in more constrained amorphous environments. Correlations between molecular mobility and barrier properties are proposed.